Analisis Penentuan Cadangan Kas Badan Layanan Umum - Aptasari, Fety Widianti; Handajani, Lilik; Fikri, Ali (E-Jurnal Akuntansi; Vol 32 No 5 (2022), 2022)
This research based on government regulation that makes the government have the right of immunity in taking more funds at a BLU which is then distributed to other BLUs, so cash reserves need to be made. This study aims to analyze the nominal cash that must be reserved by BLU University X. The amount of cash reserves must be adjusted by considering the possibility of the government taking a surplus of BLU funds and financial condition to become management capital at the beginning of the following year. This study uses a descriptive qualitative approach. Data were obtained through interviews with the financial, PNBP coordinator and expenditure treasurer. The results showed that BLU University X did not yet have a cash reserve strategy to deal with the government regulations. The implication of this research is as a consideration for BLU in formulating policies and strategies to manage cash from the remaining cash at the end of the previous year to be used as cash reserves. Keywords: Cash Reserves; Budget Absorption; Budget Surplus.